Development of Mathematics Learning Module Based on Realistic Mathematics Education (RME) Approach in SPLDV Materials - Lisa Levia Miranda; Siti Suprihatiningsih; Rizki Nurhana Friantini; Konstansia Hermiati; Pradipta Annurwanda (AlphaMath : Journal of Mathematics Education, 2022)
Learning mathematics which is still abstract makes it difficult for students to understand the material of a two-variable linear equation system. It is necessary to arrange modules with realistic content to make it easier for students to understand the material. The research aims to develop a Mathematics learning module based on the Realistic Mathematics Education (RME) approach to the Material of a Two-Variable Linear Equation System. The research method developed is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this study were validation sheets, observations, and learning outcomes tests. Validation sheet to obtain data about the results of the validation of experts regarding the module, observation sheet to see the implementation of the module. Test results to determine the average percentage of student test scores. Data analysis was carried out to obtain a suitable and qualified mathematics learning module that met the valid, practical, and effective criteria. The criteria for the level of validity, practicality, and effectiveness of the module that are considered sufficient to continue at the next stage are at least . Based on the results of the limited trial, the results obtained were very good, students felt happy and excited during the delivery process. To the illustrations in the module that were distributed to students, their response was enthusiastic and enthusiastic in working on the practice questions during the learning process. It can be seen from the results of the evaluation carried out by the students that it produced a positive response, so that the percentage of the students' positive response was the lowest at 80.49. This means that the development of this module is very useful and beneficial for students.